Effect of operative time on complications following primary total hip arthroplasty: analysis of the NSQIP database. Issue 2 (March 2021) - Sikov, Mark; Sloan, Matthew; Sheth, Neil P
Background: Long operative times in total hip arthroplasty (THA) have been shown to be associated with increased risk of revision as well as perioperative morbidity. This study assesses the effect of extended operative times on complication rates following primary THA using the most recent national data. Methods: The National Surgical Quality Improvement Program (NSQIP) database (2008–2016) was queried for primary THA. Groups were defined by operative time 1 standard deviation (1 SD) above the mean. Univariate, propensity score-matched, and multivariate logistic regression analyses were performed to evaluate outcomes. Results: Data was available for 135, 013 THA patients. Among these groups, mean operative time in the extended operative time group was 166 minutes (compared with 82 minutes). Patients undergoing longer operative times were 3.8 years younger, had a 1.5 kg/m 2 higher body mass index and had a 0.5 day longer mean length of stay. Propensity matching identified 16, 123 pairs for analysis in the 1 SD group. Longer operative time led to 173% increased risk of major medical morbidity, 140% increased likelihood of length of stay greater than 5 days, 59% increased risk of reoperation, 45% increased risk of readmission, and a 30% decreased likelihood of return to home postoperatively. There was no increased risk of death within 30 days. Conclusion: Long operative times were associated with increases in multiple postoperative complications, but not mortality. Surgeons should be advised to take steps to minimise operative time by adequate preoperative planning and optimal team communication.